Analisis Pengawasan Retribusi Pelayanan Parkir Tepi Jalan Umum Dalam Rangka Meningkatkan Penerimaan Pajak Parkir Di Kelapa Gading - Kamba, Susana Amelia; Permatasari, Mira (Jurnal Ilmu Administrasi Publik, 2024)
The receipt of the parking levy in 2022-2023 cannot meet the target that has been set. The highest achievement is only 58.69%. Research this aims to determine the results of the analysis of the supervision of public roadside parking levy services in order to increase parking tax revenue in kelapa gading in 2022/2023. This study is a descriptive qualitative research. Data collection techniques are interviews, observation and documentation. Interviews were conducted with the head of billing Unit, Head of Service Unit UPPPD Kelapa Gading District, Academic lecturers and taxpayers. The results showed that there are barriers that occur is limited tax officials and taxpayers who still do not understand the use of technology and its efforts, namely   conducting   socialization   activities   and improving services, using other social media.